(untitled) (Iranian Journal of Kidney Diseases, 2024)
Introduction. Acute kidney injury (AKI) is a frequent complication after hematopoietic stem cell transplantation (HSCT), with reported incidences ranging from 20-70% within the first 100 days post-transplant. AKI can adversely impact outcomes and survival in this patient population. Methods. This retrospective study evaluated 110 pediatric patients who underwent HSCT at Mofid Children’s Hospital, affiliated with Shahid Beheshti University of Medical Sciences, Tehran, Iran, between 2016-2021. AKI was defined and staged according to the criteria for Kidney Disease Improving Global Outcomes (KDIGO). Results. The cohort comprised 68 (61.8%) males and 42 (38.2%) females, with a mean age of 6.4 ± 4.1 years. Underlying disorders were malignant in 64 (58.1%) and non-malignant in 46 (41.9%) patients. Among the cohort, 84 (76.3%) patients underwent allogeneic HSCT, while 26 (23.7%) received autologous HSCT. Myeloablative and reduced-intensity conditioning regimens were used in 77 (70%) and 33 (30%) patients, respectively. AKI developed in 53 (48%) patients within 100 days post-transplant, with incidences of 38%, 40%, and 22% for stages 1, 2, and 3 AKI, respectively. AKI incidence was higher in allogeneic HSCT (52%) compared to autologous HSCT (17%; P = 0.023). Younger age (P = 0.033) and non-malignant disorders (P = 0.033) were associated with increased AKI risk. At the end of the study, 77 (70%) patients were alive, and 33 (30%) had deceased, with a significant positive correlation between AKI stage and mortality (P = 0.004). Conclusion. This study highlights the high prevalence of AKI among pediatric HSCT recipients, particularly those undergoing allogeneic HSCT, at a younger age, and with non-malignant disorders. Regular post-transplant renal monitoring may improve survival in this population.